Participation of the Public in Central and Local Governance: Principles, Statistics and European Experiences for Ukraine - Semianovskyi V. М. (Statistics of Ukraine, 2019)
Issues of the effective participation and cooperation of the civil society in power bodies have been a central social problem of the globe in the latest times. Although theoretical issues of participatory governance have been well developed and widely implemented, e. g. in business sector, cooperation of Power and Community pose a serious problem in the world and Ukraine in particular. The effectiveness of cooperation between Power and the civil society is downgraded by the issue the current condition of both parties, the quality of their work and their mutual trust. Also, it needs to be born in mind that this problem is a part of the triangle Power – Society – Business, and that the external environment has significant impact in the conditions of globalization. Given the Ukrainian context, it should be considered that the power system here was inherited from the Soviet Union. It is incompatible with the present-day realities, and its reform has been so far ineffective. The data from the State Statistics Service of Ukraine (SSSU) show the vast numbers of officials in local governance and central power bodies, picked up in industry-like administrative departments. The bulky apparatus of public governance being streamlined on the problem solution process in economic industries, social problems, not mentioning the ones of individual humans, can be looked at only before elections. On the other hand, according to SSSU, Ukraine has a network of rather diverse public organizations, but their total number is small. According to Eurostat, quantitative and qualitative parameters of the civil society in Ukraine lag far behind the European ones. A diversity of goals, weak consolidation of efforts, resources and methods for solving the most important problems are factors complicating the cooperation between Power and Community. Theoretical and practical aspects of the problem related with cooperation of Power and the civil society have been elaborated in Europe since long. Advanced principles and various technologies for its solution have been proposed and implemented. The first typology of the public participation in form of “public participation staircase” was admittedly made by researcher Sh. R. Arnstein. She broke the staircase into the three levels: non-participation, symbolic participation, public power. To boost the effectiveness of collaborative action, the European community has elaborated the Code of recommended norms for the participation of the public in taking public decisions. In fact, this technology is the standard of cooperation between Power and Community in Europe. The need for reform of the system for cooperation of power bodies with the civil society in Ukraine by use the European experience of cooperation is substantiated. The issues of goals, principles, methods and phases of cooperation between the power and the society, their advantages and drawbacks are highlighted.